Triplophysa lixianensis, a new nemacheiline loach species (Pisces: Balitoridae) from the upper Yangtze River drainage in Sichuan Province, South China - He, Chunlin; Song, Zhaobin; Zhang, E (Zootaxa, 2008)
Triplophysa lixianensis, a new nemacheiline loach species, is described from the Min Jiang of the upper Yangtze River drainage in Sichuan Province, South China. It can be separated from all other species of Triplophysa by having a unique combination of the following characters: posterior chamber of gas bladder greatly reduced or absent; caudal peduncle columnar with a roughly round cross-section at its beginning; anterior edge of lower jaw completely exposed or uncovered by lower lip; intestine short, forming a zigzag loop below stomach; dorsal-fin origin closer to caudal-fin base than to snout tip; pelvic fin inserted anterior to dorsal-fin origin; snout length 50.6–57.5 % of head length; eye diameter 12.3– 15.4 % of head length; caudal peduncle length 25.1–27.1 % of standard length; anal fin with five branched rays; lower lip greatly furrowed with two thick lateral lobes; and body smooth or scaleless.